Peran regulasi hukum bisnis dalam mendorong kepatuhan usaha mikro, kecil, dan menengah (UMKM): Review jurnal sistematis - Sukayasa, I Nyoman (Nur Science Institute, 2025)
Micro, Small, and Medium Enterprises (MSMEs) are a vital driver of Indonesia’s economy, yet their legal compliance level remains low due to regulatory complexity, limited tax literacy, and technological constraints. This study aims to systematically review the role of business law regulations in promoting MSME compliance, with the objective of identifying influencing factors, research gaps, and policy development directions. Using a Systematic Literature Review (SLR) approach, 27 peer-reviewed journal articles published between 2013 and 2023 were analyzed. The selection process followed inclusion and exclusion criteria, and reporting adhered to the PRISMA flow diagram to ensure systematic and valid results. The findings reveal that regulatory clarity, ease of licensing, tax education, digital infrastructure, and government support programs are key factors influencing MSME compliance. However, challenges such as inconsistent policy implementation and limited access to legal resources persist. The study concludes that comprehensive, accessible, and technology-driven regulatory frameworks are essential to improving compliance levels, thereby enhancing the sustainability and competitiveness of MSMEs in Indonesia.